Neighborhoods matter. A systematic review of neighborhood characteristics and adolescent reproductive health outcomes. (November 2018) - Decker, Martha J.; Isquick, Sarah; Tilley, Lana; Zhi, Qi; Gutman, Anya; Luong, William; Brindis, Claire D.
Abstract: This systematic review examines the relationship between neighborhood characteristics and adolescent pregnancy, contraceptive use, sexual initiation, and birthrate. Several studies found a significant association between higher poverty and increased adolescent birthrate, pregnancy, and earlier age at sexual initiation. Unsafe neighborhoods were associated with earlier sexual initiation and increased adolescent pregnancy. Mixed results were found for neighborhood racial or ethnic composition. Lower collective efficacy and social support were associated with increased rates of adolescent pregnancy and earlier age at sexual initiation. Improved definitions of neighborhoods, as well as research on interactions between structural factors and social processes during adolescence is needed. Highlights: Neighborhood characteristics may influence adolescent reproductive health outcomes. Neighborhood disadvantage is associated with earlier sexual debut and pregnancy. Increased adolescent pregnancy is associated with neighborhood violence or disorder. Higher collective efficacy is associated with lower teen birthrates.